2018
DOI: 10.1080/01677063.2018.1497630
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic gating of long-lasting synaptic potentiation in the hippocampus: from neurobiology to translational biomedicine

Abstract: Altered synaptic strength underlies information storage in neural circuits. Neuromodulatory transmitters such as norepinephrine (NE) facilitate long-lasting synaptic plasticity by recruiting and modifying multiple molecular elements of synaptic signaling, including specific transmitter receptors, intracellular protein kinases, and translation initiation. NE regulates multiple brain functions such as attention, perception, arousal, sleep, learning, and memory. The mammalian hippocampus receives noradrenergic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 144 publications
(176 reference statements)
0
10
0
Order By: Relevance
“…NE through activation of ARs increases the strength of synaptic transmission at glutamatergic synapses and modifies the synapses via cAMP signals and protein synthesis to increase long-term plasticity occurring over minutes to hours in duration ( Hopkins and Johnston, 1984 ; Dahl and Sarvey, 1989 ; Harley, 1991 ; Bröcher et al., 1992 ; Harley and Sara, 1992 ; Huang and Kandel, 1996 ; Bramham et al., 1997 ; Erickson et al., 1997 ; Katsuki et al., 1997 ; Thomas and Palmiter, 1997a ; Thomas and Palmiter, 1997b ; Thomas and Palmiter, 1997c ; Izumi and Zorumski, 1999 ; Watabe et al., 2000 ; Walling and Harley, 2004 ; Maity et al., 2020 ). As the signals involves cAMP, most previous studies have concluded that the sole AR in mediating NE effects on long-term plasticity have been the β-ARs ( Maity et al., 2015 ; Hansen and Manahan-Vaughan, 2015 ; Nguyen and Gelinas, 2018 ). However, α 1 -ARs have been shown to mediate increased cAMP generation particularly in brain tissue independent of β-AR effects ( Huang and Daly, 1972 ; Schultz and Daly, 1973 ; Stone et al., 1986 ; Stone et al., 1987 ).…”
Section: Long-term Synaptic Plasticitymentioning
confidence: 99%
“…NE through activation of ARs increases the strength of synaptic transmission at glutamatergic synapses and modifies the synapses via cAMP signals and protein synthesis to increase long-term plasticity occurring over minutes to hours in duration ( Hopkins and Johnston, 1984 ; Dahl and Sarvey, 1989 ; Harley, 1991 ; Bröcher et al., 1992 ; Harley and Sara, 1992 ; Huang and Kandel, 1996 ; Bramham et al., 1997 ; Erickson et al., 1997 ; Katsuki et al., 1997 ; Thomas and Palmiter, 1997a ; Thomas and Palmiter, 1997b ; Thomas and Palmiter, 1997c ; Izumi and Zorumski, 1999 ; Watabe et al., 2000 ; Walling and Harley, 2004 ; Maity et al., 2020 ). As the signals involves cAMP, most previous studies have concluded that the sole AR in mediating NE effects on long-term plasticity have been the β-ARs ( Maity et al., 2015 ; Hansen and Manahan-Vaughan, 2015 ; Nguyen and Gelinas, 2018 ). However, α 1 -ARs have been shown to mediate increased cAMP generation particularly in brain tissue independent of β-AR effects ( Huang and Daly, 1972 ; Schultz and Daly, 1973 ; Stone et al., 1986 ; Stone et al., 1987 ).…”
Section: Long-term Synaptic Plasticitymentioning
confidence: 99%
“…Noradrenergic fibers project from the locus coeruleus to innervate the hippocampus, which expresses betaadrenergic receptors (β-ARs) that bind NE (Hillman et al 2005). Activation of β-ARs by NE engages signaling cascades that facilitate long-term neural plasticity (Stanton and Sarvey 1984;Harley et al 1996;Katsuki et al 1997; for review, see Nguyen and Gelinas 2018) and memory formation (Izquierdo et al 1998;Straube et al 2003;Lemon et al 2009;for review, see O'Dell et al 2015). Activation of β-ARs in area CA1 of the hippocampus, a brain structure critical for memory formation (Scoville and Milner 1957;Zola-Morgan et al 1986;Eichenbaum 2000), facilitates activity-dependent increases in synaptic strength (Thomas et al 1996;Gelinas and Nguyen 2005; for review, see O'Dell et al 2015).…”
mentioning
confidence: 99%
“…We found here the memory retention and learning course were both improved in WD subject, while Fos-expression in LC, as well as in LC-NE projecting regions relevant for working memory, dorsal hippocampus and prefrontal cortex, were significantly increased. NE facilitates synaptic plasticity by recruiting and modifying multiple molecular elements of synaptic signaling, including specific transmitter receptors, intracellular protein kinases, and translation initiation have been extensively reported (Maity et al, 2015; Nguyen and Gelinas, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The LC-NE system modulates some of the most salient brain functions, such as arousal, learning and memory and the cognitive response to stress (Berridge and Waterhouse, 2003; Atzori et al, 2016). At the synaptic level, NE facilitates synaptic plasticity by recruiting and modifying multiple molecular elements of synaptic signaling, including specific transmitter receptors, intracellular protein kinases, and translation initiation (Maity et al, 2015; Nguyen and Gelinas, 2018). All such LC-NE functions are strongly aligned with the levels of LC neuronal activity.…”
Section: Introductionmentioning
confidence: 99%